Pemberdayaan Usaha Mikro Kecil Menengah melalui Perlindungan Hak Merek berdasarkan Undang-Undang Nomor 20 Tahun 2016 untuk Peningkatan Daya Saing Usaha - Kaniasari, Endah; Fitryantica, Agnes (Postulat, 2024)
"Enhancing business competitiveness and empowering Micro, Small, and Medium Enterprises (UMKM) is crucial for sustainable economic development. Law Number 20 of 2016 serves as a legal policy, with trademark protection being a key aspect in strengthening the position and contribution of UMKM in an increasingly complex market competition. This research explores the roles and challenges faced by UMKM. Through analysis of various related literature, it is found that UMKM often encounter obstacles in understanding and implementing trademark protection.This study adopts a normative juridical approach through literature review to identify concepts relevant to the issues of trademark protection for UMKM. The research results indicate that the legal policies governing UMKM, such as Republic of Indonesia Law Number 20 of 2008 concerning UMKM and Law Number 20 of 2016, can serve as government methods to provide business protection to UMKM through the protection of their intellectual property in the form of trademarks. The recognition of trademarks shared among UMKM serves as a means to protect their intellectual property against large industries or other business entities that may attempt to obtain intellectual property owned by UMKM without proper authorization. Disputes arising from trademark ownership are typically resolved based on the trademark certificate as evidence of ownership, unless the trademark is invalidated through trademark litigation brought before the Commercial Court. UMKM associations can serve as bridges for UMKM to access information, business networks, and even skill development opportunities, thereby enhancing the capabilities of UMKM.